Acciones de enfermería y su relación con la prevención de la desnutrición infantil en preescolares del jardín de infantes “Sofía García” del cantón Yaguachi periodo octubre 2019-abril 2020. - Bastidas Gavilánez, Gabriela Katherine (2020)
This research work was carried out in the “Sonia García” garden of the city of Yaguachi, which is an institution dedicated to providing education services to children under five years of age, where this research had as main objective to analyze the actions of Nursing and its relationship with the prevention of child malnutrition, because this disease is considered of social origin and most parents do not know what are the factors, causes or symptoms caused by the appearance of this pathology in children during its first years of life. In order to carry out this research, quali-quantitative approaches were applied because numerical information and essential characteristics of the variables studied were collected, in the same way the types of exploratory, descriptive and cross-sectional research were used, because they allowed to explore and Describe the relevant data obtained from the application of the survey and anthropometric evaluation techniques through the implementation of information collection instruments such as questionnaires for parents and anthropometric measurement related to infants. The research yielded the following results that most parents do not know the importance and benefits of performing an anthropometric control of their children on a regular basis to detect any abnormality in their body during their development, there are also infants who have height, weight and BMI above and below normal according to the percentiles for these ages determined by the World Health Organization. In conclusion, childhood malnutrition is a disease that affects the normal development and growth of infants as their age progresses, for this reason, it is necessary to promote information campaigns on the prevention of this disease in infants.